The Impact of Smoking, Including Hookah, on the Human Body - Elena Emelina (Journal of Global Pharma Technology, 2016)
Smoking is a social problem in society. For smokers, the problem is to quit smoking, for non-smokers-to avoid the influence of smokers and not